Application of Samuelson - Stone linear expenditure system to food consumption in Ireland - Casey, Michael G. (Economic & Social Studies, 1973)
The principal aim of this paper is to offer a structural analysis of the pattern of food consumption in Ireland over a period of twenty-one years. Such an analysis may also be useful as a basis for projections, although this aspect of the subject is only briefly examined here.
Keywords: Food consumption; Ireland